La « révolution numérique » : une révolution technicienne entre liberté et contrôle - André Vitalis (Communiquer)
The “digital revolution” understood through the thought of Jacques Ellul is a technical revolution with contrasting effects. It has paradoxically created new spaces of freedom at the cost of greater control over individual freedoms. Also, it has not constituted a solid basis for a liberating political revolution as assumed by the theories of multitudes, cognitive capitalism or post-media era. To realize the revolution needed in this 21st century, we must set objectives and boundaries to digital technical development by prioritizing those that promote self-government and human knowledge.